Práticas de leitura e letramento na EJA: a desenvoltura de competências leitoras como pressuposto para o usufruto da cidadania - Brito, Edenia Cesarina de (2016)
In this dissertation we can look closely at the Education of Young and Adults (EJA). The difficulties evidenced in this type of teaching have always worried us especially about reading. Our interest in this subject is justified by the understanding that since the EJA is aimed at the segment of the population that for various reasons did not have access to school in the regular mode and / or at the appropriate age, it is of crucial importance to optimize the time for this public in the In order to enable the development of appropriate skills and abilities to fully enjoy their citizenship in an eminently literate society, as well as the official documents governing education in Brazil. Thus, we highlight the practice of reading and literacy as a necessary and indispensable strategy for the success of students of this type of teaching and for the full exercise of citizenship. Based on this recognition we set out as the main objective of our research to identify the difficulties related to the reading competence of the students and present a proposal of intervention to favor the development of this competence and consequently provide better performance in citizen social practices. The study was performed in an EJA room of cycle IV of a Municipal School of João Pessoa, Paraíba. We take as a guiding thread to approach such competence the descriptors - to find information explicit and implicit in a text; Infer the meaning of a word or expression; Identify the theme of a text and distinguish a fact from an opinion concerning it - contained in the first topic entitled Procedures of reading presupposed in the Reference Matrix of the Brazil Proof for the final cycles of Elementary School. We base our research on official documents that govern education in Brazil, but specifically in relation to the EJA, such as the Federal Constitution (CF), the Law of Guidelines and Bases (LDBEN), the National Curricular Parameters (PNC), The National Basic Education Guidelines and the Reference Matrix of the Brazil Test. As for the reading approach our study is based on authors such as Kleiman (2013, 2005), Mollica & Leal (2009), Soares (2001), Koch & Elias (2014), Solé (1998), Antunes which discuss the conceptions of language, language, literacy and reading, with which we work. And to support our methodological choice for action research, whose assumptions point to the need to verify and interfere with reality, we rely on studies by Thiollent (2011). From this perspective we conducted a descriptive and exploratory study. The data that constitute the corpus of the research were collected through the application of three questionnaires. The first met the socio-cultural diagnostic objective of the students. The second one was applied to identify the critical points of the reading competence among which we highlight the difficulty in relation to reflective reading. And the latter, applied after the intervention, served as a guide to the results obtained on which we could affirm that the interventions contributed to develop student's reading competence.